Hematological and iron status in aerobic vs. anaerobic female athletes: an observational study - Osman, D. A.; Elassal, M. I.; Hamada, H. A.; Hamza, R. H. S.; Zakaria, H. M.; Alwhaibi, R.; Abdelsamea, G. A. (Frontiers in Sports and Active Living, 2024)
Introduction: Physical training induces iron status impairment in athletic females in the short term and over prolonged periods. Nevertheless, the existing literature lacks a comprehensive evaluation of the differential impacts of aerobic vs. anaerobic training on hematological indices and iron status among adolescent female athletes. The aim of this study was to assess the hematological factors and iron status in aerobic vs. anaerobic training in athletic females.